Previous Pedagogical Beliefs of Freshman of Teacher Education. - Rivas-Flores, José Ignacio; Pérez Ferra, Miguel; Leite-Méndez, Analía Elizabeth; Quijano López, Rocío; Núñez, Claudio (My University, 2013)
This paper is part of a research project about how students of teacher education elaborate their professional identity. Through a inquiry on their life stories, the research aims to understand and analyse the experiences of these students along their primary and secondary education, their experiences in university classrooms, and the incidence of these experiences, as well as those generated in schools, in the early years of his teaching career. The project, called “the professional identity of the teacher education”, involves the universities of Almeria, Cadiz, Cordoba, Granada, Jaen and Malaga, in Andalusia (Spain) and the universities of the State of Santa Catalina and Santa Catalina Federal, in Brazil. It addresses the fact that students who begin their studies in teacher education, come with ideas and beliefs of their experiences in the years as pupils _ at Primary and Secondary Education. In these circumstances, the initial phase of teacher education is a complex process in which many students have to give up preconceived ideas about the nature of teaching. These ideas can act as constraints in the learning process as future teachers. Students usually do not have the possibility to see how teachers facing major changes in their teaching strategies based on reflection on practice, since the model of education in Universities is primarily academic and literary. For this reason they have trouble to deepen the possible unsuitability of their previous ideas about education. Also the students' prior beliefs prepared about teaching decisively influence how they interpret the didactic training received in college. Furthermore, these students' prior beliefs about teaching have a very important influence on how they interpret the didactic training received in college. Therefore they reproduce, in their performance as students, the same patterns learned in school. In this way the professional learning that has taken place in their school years is strengthen. We suggest the appropriateness of dealing the analysis of the students of teacher education previous pedagogical beliefs of through the following objectives: a) Understanding and analysing the personal and formative profiles of freshmen teacher education; b) determining what effects have the previous pedagogical beliefs of students the first year of teacher education on how to integrate the professional lessons received in college c) encourage teacher education students the development of criteria to enable them to recognize and analyse beliefs they have on the previous teaching and justify their opportunity.
Presentado en ECER 2013, Estambul, del 4 al 9 de setiembre de 2013
Keywords: Profesores de enseñanza primaria - Formación profesional; Educación; Formación inicial profesorado primaria